The relationship of anthropometric measures to different types of breaststroke kicks - Nimz, R.; Rader, U.; Wilke, K. (Swimming Science V, 1988)
In breaststroke swimming the kick has an important influence on propulsion. Therefore, teaching and using the most effective type of breaststroke kick are both necessary and desirable. At the moment the whip kick is the most effective type of breaststroke kick (Counsilman, 1977; Maglischo, 1982). This form is characterized by limited braking resistance an big traction areas, which can be used for propulsion (Volker & Wilke, 1974). The use of a whip kick seems to be very difficult because often it results in an uneconomical kick when performing the breaststroke. The purpose of the present investigation was to determine whether anthropometric values as well as functional angles of amplitude for movements within the lower limb region were determining factors for a certain type of breaststroke kick. For that purpose, the flexibility of joint movements observed during a regular breaststroke kick were determined. This research was confined to three symmetrical types of kicks: whip kick, wedge kick, and a kick ""ith plantar flexed feet.